Property Ladder : Design for Profit - Beeny, Sarah and Philimore, Jane (London Cassell Illustrated, 2009)
Includes the various design tools you need to design your home - from colour schemes and furniture to storage solutions, aspect and furniture. Including case studies from a range of real-life projects, this book reveals success stories, along with examples of bad design and development failures and everything you should and shouldn't do.
Include Color Illustration and Index
Keywords: Do-it-yourself work -- Dwellings--Maintenance and repair